2023
DOI: 10.1590/1677-5449.202201472
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral variation in the branching pattern of the subclavian artery: an unusual finding with clinical implications

Abstract: The subclavian artery is a significant branch of the aortic arch. We present a rare case of a bilateral variation in the branching pattern of the subclavian artery, observed in an adult male cadaver aged 70 years. On both the sides of the neck, all the branches of the subclavian artery took their origin from its first part. There was a rare occurrence of a cervicodorsoscapular trunk, which gave rise to superficial cervical, suprascapular, and dorsal scapular arteries. The same branching pattern was observed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There is significant variability in the course of the branches of the axillary artery and no clear fluoroscopic landmarks as to their course. 4 , 5 In this case, the axillary vein was punctured at the lateral border of the first rib, a common site of venous access, and the pseudoaneurysm is seen to form near this site. Computed tomography angiography proved useful in our and other cases to diagnose the site of bleeding and imaging was not significantly affected by the presence of the pacemaker, supporting the use of this imaging modality to evaluate postdevice bleeding complications.…”
Section: Discussionmentioning
confidence: 92%
“…There is significant variability in the course of the branches of the axillary artery and no clear fluoroscopic landmarks as to their course. 4 , 5 In this case, the axillary vein was punctured at the lateral border of the first rib, a common site of venous access, and the pseudoaneurysm is seen to form near this site. Computed tomography angiography proved useful in our and other cases to diagnose the site of bleeding and imaging was not significantly affected by the presence of the pacemaker, supporting the use of this imaging modality to evaluate postdevice bleeding complications.…”
Section: Discussionmentioning
confidence: 92%
“…Takafjui et al further demonstrated that the TCA was absent in 15.3% of cases (22/144 sides of the neck) and in another 22 cases the TCA branched independently from the TCT and SA (15.3%) [ 5 ]. Another study by Kumar et al reported a bilateral absence of TCA on a single cadaveric specimen [ 12 ]. In our case, the TCA was absent on the right side of the neck from the TCT and from the SA completely without any independent branches from these vessels providing blood supply to the trapezius muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving cadaveric neck dissections, computed tomography angiographies (CTA), and case reports have demonstrated variations in the branching of the TCT [ 1 , 3 – 7 ]. Studies have also reported anatomical variations of the SSA [ 8 11 ], TCA [ 5 , 12 ] and DSA [ 13 , 14 ]. However, the literature on the absence of the SSA and TCA is limited [ 5 ].…”
Section: Introductionmentioning
confidence: 99%